La nueva pobreza en la Argentina - Minujin Z., Alberto; Kessler, Gabriel, 1964- ([Buenos Aires, Argentina : Editorial Planeta, 1995)
"Effectively combines detailed case studies and quantitative survey data to provide an overview of impoverishment patterns in Argentina in early 1990s. Intended primarily for general rather than academic audiences"--Handbook of Latin American Studies, v. 57.
Incluye referencias bibliográficas (p. [271]-278).
Keywords: Argentina; Pobreza; Salud; Educación; Identidad cultural; Capital social; Juventud; Cambio cultural; Empobrecimiento; Precariedad